Measuring the effectiveness of NMÍ's incubators. A study of public business incubators in Iceland - Kristinn Árni L. Hróbjartsson 1989- (2014)
In recent years, entrepreneurship and innovation has gained traction in the public dis-course and the attention of policymakers. One of the tools available to spur entrepre-neurship is operating business incubators - organizations which provide shared office space and business consultation and services to startups. In Iceland, Innovation Center Iceland (NMÍ) is the largest operator of incubators. NMÍ operates four incubators as well as co-operating with other organizations on several others. The objective of this re-search was to analyze the incubators run by NMÍ, measure their effectiveness, and compare this with the results of similar research done on incubators elsewhere. NMÍ’s incubators were analyzed and compared to suggested best practices in incubator opera-tion. A survey, based on a four dimensional model to measure the effectiveness of incu-bators was sent to previous clients of NMÍ’s incubators. The results, which are not sta-tistically significant, showed that companies incubated at NMÍ report a considerably lower success rate than at other incubators in the USA and Europe, and NMÍ’s incuba-tors did not implement a substantial part of best practices suggested in the literature, which possibly explains the lower success rate.